PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DAN TEAM GAMES TOURNAMENT BERBANTUAN MEDIA KARTU KATION ANION TERHADAP HASIL BELAJAR KIMIA - Anisa Rosmalara; Rina Elvia; Salastri Rohiat (University of Bengkulu, 2019)
This study aims to determine the differences in student chemistry learning outcomes between classes that apply the Student Teams Achievement Division (STAD) learning model with a class that applies the Team Games Tournament (TGT) learning model to chemical compounds. This type of research is quasi-experimental with a population of class X IPA Academic Year 2018/2019 which amounts to 204 students. Samples were obtained from the results of the normality test and homogeneity test, namely class X IPA 4 which applied the STAD learning model with cation anion media and class X IPA 6 which applied the TGT learning model with anion cation card media. This study was conducted in January-March 2019. Analysis of the data used is the average (mean), normality test, homogeneity test, and hypothesis testing (u test). In general, the two models were able to improve learning outcomes, where the STAD learning model obtained higher results, namely 79.723. Data on students' chemistry learning outcomes were obtained from the pretest and posttest values where the average value of the increase in cognitive learning outcomes for the STAD class and the TGT class was 57,222 and 46,944. Through a series of statistical tests hypotheses were tested using the u test with a significant level (? <0.05) indicating the value (Sig. 2-tailed) of 0,000. This shows that there are significant differences in learning outcomes between classes applying the STAD learning model assisted by anion cation cards with classes that apply the TGT learning model assisted by anion cation cards.